2006
DOI: 10.1128/aac.00684-06
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Biofilms Produce Antifungal-Tolerant Persister Cells

Abstract: Fungal pathogens form biofilms that are highly recalcitrant to antimicrobial therapy. The expression of multidrug resistance pumps in young biofilms has been linked to increased resistance to azoles, but this mechanism does not seem to underlie the resistance of mature biofilms that is a model of in vivo infection. The mechanism of drug resistance of mature biofilms remains largely unknown. We report that biofilms formed by the major human pathogen Candida albicans exhibited a strikingly biphasic killing patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
411
4
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(438 citation statements)
references
References 51 publications
11
411
4
6
Order By: Relevance
“…10 It became imperative to remove these biofilm-attached implants and devices, otherwise they may disseminate candidiasis infection. 52 Besides the multifactorial phenomenon, [11][12][13][14][15] the unique properties of Candida biofilm matrix materials thwart antimicrobial activity against well-ensconced Candida cells as compared to planktonic cells. The chemical composition of ECM of Candida biofilm has not been not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 It became imperative to remove these biofilm-attached implants and devices, otherwise they may disseminate candidiasis infection. 52 Besides the multifactorial phenomenon, [11][12][13][14][15] the unique properties of Candida biofilm matrix materials thwart antimicrobial activity against well-ensconced Candida cells as compared to planktonic cells. The chemical composition of ECM of Candida biofilm has not been not fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Among the most important factors are biofilm matrix or exopolmeric substance (EPS), high density of cells in biofilm, presence of presister cells, and drug-efflux pumps. [11][12][13][14][15] Ambient matrix or EPS produced by sessile cells of biofilm recently gained the spotlight and imparting the impregnation of drug molecules and putative charge barrier. 16,17 Recently, photodynamic therapy (PDT) emerged as an alternative to conventional treatment of infections caused by C. albicans.…”
Section: Introductionmentioning
confidence: 99%
“…However, their importance in chronic infections is becoming increasingly clear, motivating more researchers to tackle the issue of fungal biofilms. LaFleur et al (2006) reported for the first time the presence of a population of antifungal-tolerant cells within a Candida biofilm, much resembling the bacterial persister cells found in P. aeruginosa and E. coli planktonic and biofilm populations. Contrary to bacterial populations, planktonic Candida populations do not produce persister cells refractory to the lethal action of antibiotics.…”
Section: Candidiasismentioning
confidence: 99%
“…57 Persistence is not restricted to bacteria since, e.g., it has also been observed in the fungus Candida albicans. 58 It is epigenetic in nature, even though many genes by know are known to affect the frequency by which persisters are formed. 15,59,60,65 Since persisters are extremely slow growing or totally growth arrested, it has been speculated that expression of toxins might stochastically drive a fraction of a bacterial population into the persister state.…”
Section: Ta Systems and The Persister Connectionmentioning
confidence: 99%